1973
DOI: 10.1254/jjp.23.329
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Chronotropic Effects of Catecholamines and Tyramine on the Sa Node of the Dog Heart in Situ

Abstract: Abstract-The relative potency of chronotropic effects of dopamine (DA), l-nor epinephrine (NE), l-epinephrine (EP), l-isoproterenol (ISO) and tyramine (TY) was determined by direct application into the sinus node artery of the in situ canine heart (n=10), which was treated with atropine. The order of potencies of chronotropic effect of these amines was ISO>NE=EP>DA ?? TY. The ratio of doses required to produce 50% increase in sinus rate was ISO: NE: EP: DA: TY=1/30: 1: 1: 10: 10. At … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
3
0

Year Published

1973
1973
1976
1976

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
3
3
0
Order By: Relevance
“…Therefore, positive chronotropic and inotropic responses to octopamine were mainly due to its indirect effect on the heart. Furthermore, effects of octopamine were not influenced by tetrodotoxin which blocks effects of nicotine as reported previously (Chiba et al 1973). As tyramine effects were not prevented by tetrodotoxin (Hashimoto and Chiba 1969;Chiba 1975a, b), the indirect effect of octopamine may be due to a tyramine-like action.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Therefore, positive chronotropic and inotropic responses to octopamine were mainly due to its indirect effect on the heart. Furthermore, effects of octopamine were not influenced by tetrodotoxin which blocks effects of nicotine as reported previously (Chiba et al 1973). As tyramine effects were not prevented by tetrodotoxin (Hashimoto and Chiba 1969;Chiba 1975a, b), the indirect effect of octopamine may be due to a tyramine-like action.…”
Section: Discussionsupporting
confidence: 80%
“…The duration of action of octopamine was significantly longer than that of dopamine or norepinephrine. Previously Chiba et al (1973) demonstrated that dopamine given into the cannulated sinus node artery induced much longer sinus acceleration than norepinephrine or epinephrine. Then, it was demonstrated in the in situ and isolated atrium preparations that dopamine-induced positive chronotropic and inotropic effects were signfiicantly suppressed by treatment with desmethylimipramine (Chiba et al 1974;Chiba 1975a, b).…”
Section: Discussionmentioning
confidence: 99%
“…When tyramine was administered into the sinus node artery, sinus accelera tion was dose-dependently induced as reported previously (James and Nadeau 1964; Chiba et al 1973). It is well known that this tyramine action is blocked by DMI treatment.…”
Section: Effect Of Dmi On Tyramine-induced Sinus Accelerationsupporting
confidence: 68%
“…These observations indicate that the sinus node preparation is more resistant to the blocking effect of DMI on the neuronal uptake of the amines (Iversen, 1967) as well as to depletion of NA by reserpine: the effect of dopamine on the sinus node is fundamentally not different from that on the papillary muscle. Thus, findings with reserpine and DMI support the view (Bejrablaya et al, 1958;Lee & Yoo, 1964;Farmer, 1966;Tsai et al, 1967;Chiba, Hashimoto & Hashimoto, 1973;Neuvonen & Westermann, 1973) that both the positive inotropic and the positive chronotropic responses to dopamine are mediated partially by a direct and partially by an indirect stimulant effect on ,B-adrenoceptors.…”
Section: Mechanism Ofaction Of Dopaminesupporting
confidence: 63%